Research on MTU in Dual Stack Environment in Telecom IPMAN - Yongming Yan (Dianxin kexue)
Currently, there are various MTU processing mechanisms in dual stack environment in telecom IPMAN, but they have respective shortages and appropriate usage scenarios. Based on the analyses of above problems, the relatively feasible solution was provided, and the expected ideal target was discussed.